Watermelon Germplasm with Resistance to Whitefly-transmitted Viruses - Alex Luckew; Nebahat Sari; Swikriti Pandey; Ted McAvoy; Alvin M. Simmons; Geoffrey Meru; Cecilia McGregor (HortScience)
The current management of whiteflies is largely dependent on insecticides. However, pesticides are costly and do not provide effective control of whitefly-transmitted viruses (WTVs). However, breeding for resistant cultivars can provide a more effective and sustainable solution. Twenty-one Citrullus genotypes, including 10 C. lanatus, four C. mucosospermus, six C. amarus, and one C. ecirrhosus, were evaluated to determine their resistance to three WTVs common in Georgia in field trials for 2 years. Phenotypic data were collected weekly to determine viral disease severity, and the cumulative season data were calculated as the area under the disease progress curve. Leaves were collected 5 weeks after transplanting (WAT) in 2022 and at 7 WAT in 2023 to determine the viral loads of Cucurbit leaf crumple virus (CuLCrV), Cucurbit yellow stunting disorder virus (CYSDV), and Cucurbit chlorotic yellows virus (CCYV) via a quantitative polymerase chain reaction. The CuLCrV and CYSDV viral loads were higher in 2022 than those in 2023, whereas the CCYV load was higher in 2023. Three accessions (PI 494528, PI 595203, and Grif 16444) outperformed the cultivars for viral disease resistance and CuLCrV load (2022). In 2022, there was a significant difference among cultivars regarding the CYSDV load, with ‘AU-Producer’, ‘Crimson Sweet’, and ‘Estrella’ having lower loads than those of ‘Charleston Gray’ and ‘Sugar Baby’. There were no statistical differences in CCYV loads between the best-performing accessions and ‘Charleston Gray’. Grif 16444 is a C. ecirrhosus accession, and this species has resistance to whiteflies. The two C. mucosospermus accessions (PI 494528 and PI 595203) provide a valuable resource for breeders to develop CuLCrV resistance in watermelon (C. lanatus) because there is no reproductive barrier between the two species.